2011
DOI: 10.1097/scs.0b013e31822ea6e8
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Cementoblastoma in a Child

Abstract: Cementoblastoma is a rare benign tumor that almost always occurs in the premolar or molar region and more commonly in the mandible than in the maxilla. We present a unique incisor maxillary cementoblastoma in an 11-year-old child not previously described. To our knowledge, only 2 maxillary cases, both related to canine teeth, were described in the international literature. Thus, the aim of this article was to discuss the clinical presentation, diagnosis, and subsequent treatment of a patient with a cementoblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The treatment of choice is complete removal of the lesion with extraction of the associated tooth or teeth 34. Curettage and peripheral ostectomy have been advocated due to the high recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of choice is complete removal of the lesion with extraction of the associated tooth or teeth 34. Curettage and peripheral ostectomy have been advocated due to the high recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…The typical clinical presentation of cementoblastoma includes: male or female under 30-years-old, can be painful or asymptomatic, swelling, located in the premolar/molar region, [1,4,6,10,11,12,13], more frequently in the mandible [1,4,6,7,10,12,11,12,13,14,15,16]. Previous studies have reported the occurrence of cementoblastoma in the right maxillary and mandibular canine [6,8], right upper posterior tooth region [1], maxillary central incisor [7], mandibular first molar [14] and maxillary right first molar [4]. In the case described here, a tumor was identified in the left posterior maxilla of a 52-year-old female.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cementoblastomas are located in the mandible, most commonly in the molar region [1,2,4,5,6,7]. There is no gender predisposition [2,6,7,8], and the age of occurrence ranges from 8 to 44 years [2], with the highest incidence in the second and third decades of life [2,4,6,7,8,9]. This paper describes an unusal case of a patient who was diagnosed with cementoblastoma based on radiographic, surgical, and histological findings.…”
Section: Introductionmentioning
confidence: 99%
“…On rare occasions, an impacted tooth, multiple teeth, or a deciduous tooth may be affected as well1578. To our knowledge, there have been 8 reported cases of cementoblastoma that developed on anterior jaws in the literature910111213141516, with only two of them located in the mandible910. One case was related to an impacted permanent incisor9, while the other case was related to a deciduous incisor10.…”
Section: Discussionmentioning
confidence: 99%